2020
DOI: 10.3390/ma13102331
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology and Mechanical Properties of ESD Coatings before and after Laser Beam Machining

Abstract: Electro-spark deposition (ESD) and laser beam machining (LBM) are the technologies using the concentrated energy flux. This paper deals with the issue of the impact of laser modification on the morphology and mechanical properties of carbide/copper coatings produced by electro-spark treatment. The coatings were applied to C45 carbon steel samples using the EIL-8A device. The following three types of electrodes made using the powder metallurgy (PM) hot pressing technique, from copper and tungsten carbide powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Stress values in HAZ are elevated with respect to BM, and the values calculated in the base material are relatively low. Due to high energy density in the LBW, heat accumulation compare to conventional welding methods is low, therefore stress-strain value are lower (Radek, 2020). The stress states in the welded joint need to be controlled; however, the obtained results shows that no additional heat treatment is required.…”
Section: Laser Welding Of Trial Jointsmentioning
confidence: 99%
“…Stress values in HAZ are elevated with respect to BM, and the values calculated in the base material are relatively low. Due to high energy density in the LBW, heat accumulation compare to conventional welding methods is low, therefore stress-strain value are lower (Radek, 2020). The stress states in the welded joint need to be controlled; however, the obtained results shows that no additional heat treatment is required.…”
Section: Laser Welding Of Trial Jointsmentioning
confidence: 99%
“…Goeke and Emmelmann [ 44 ] performed experiments for the investigation of the influence of materials properties on the cut quality. Radek et al [ 66 ] performed the experimental investigation in laser cutting assisted modification by electrode spark deposition to analyze the surface microhardness, porosity, and adhesion. It was found that the aforementioned mechanical properties of the modified copper-tungsten electrodes are significantly influenced by the machined surface morphology.…”
Section: Properties Of Cut Materials In Co 2 Lasmentioning
confidence: 99%
“…Furthermore, much attention is paid to studying the effect of thermal cycling modes on hard alloys’ mechanical and tribological properties. The processes of WC material fabrication by electro spark deposition (ESD) and laser beam machining (LBM) methods and also Cr-WC electrodeposition by direct (DC) and pulsed (PC) currents are topical [ 15 , 16 ]. WC production simplification and cheapening tasks deserve particular attention [ 17 ].…”
Section: Introductionmentioning
confidence: 99%